Evaluasi Sistem Informasi Penjualan Pada PT XYZ - Nelly, Nelly; Hendarti, Henny; Mariani, Vini (Bina Nusantara University, 2013)
The study aims to evaluate the sales information system of PT XYZ whether the system supports the company's goals, as well as to determine the problem and control done by the company. Literature study and field studies through observation, interviews and checklists are implemented. The results of this evaluation are weaknesses in information systems presented on matrices of risk assessment and audit reports. The evaluation discovers the weaknesses of each control which are the potential risks and recommendation need. The controlimplemented by the company still needs to be improved further, particularly in the controls of input and output which are still weak.